(3caGjI GdWGdH aj fbO cdGe GdTGYQ hGdcGJHs - (3fUQ Gddg Hf eMeO Hf eMeO Hf YHO GdcQje GdTjHGfqj, GdLRQj, CHh GdaJM, VjGA GdOjf, GdeYQha HGHf GdCKjQ GdcGJH,J (B637 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYRjR GdLHGQ HGH GdHOjY hjTJed Ydi CfhGY cKjQI CYde Cf CUd GdHOjY GdfGOQ GdZQjH hefg GdSehGJ (B" (3dCfg CfTGgf Ydi ZjQ eKGd SGHb s
(3BNQgG (B:s
(3hGdYWGQ ai GdbhGai (B: (3GdJVejf , McGg GdNdjd Je GdcJGH hGdMeO ddg hMOg s
(3GdfSNI HQSe GdCejQ Sja GdOjf CHj HcQ Hf GdCMeOis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B98s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN eMeOs
Keywords: (3GdCOHs